PENGARUH CITRA MEREK,PERSEPSI HARGA,DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN YANG BERDAMPAK PADA LOYALITAS KOSMETIK BERLABEL HALAL âWARDAHâ - Risti Bunga Pertiwi, 12.05.51.0016; Rizal Rivai, Alimuddin (Students Journal of Economic and Management, 2016)
The research had an intention to examine the influences of brand image, price preception and the quality of product toward the customerâs satisfaction that affecting the loyalty of using the product. The population of this research are the user of Wardah cosmetics in Semarang with the total sampel of 100 correspondents that has been taken by purposive sampling technique. The research study of this final project proposes seven hypothesis that been tested using linier regression with data processing program spss 16. Based on that statistical experimentantion, I got a result that : brand image has a positive effect and has a significance relation with the satisfaction, price perception has a positive effect and has a significance relation with the satisfaction and the quality of product have a positif effect and significance relation with the satisfaction. The satisfaction it self has a positive impact in loyalty of the customers, the brand image has a positive effect loyalty pf the customers, price perception has a positive effect in loyalty of the customers. But, the quality of product has no positive effect and non-significance result toward the loyalty, because the customers have to feel the satisfaction from a certain product first that can lead into a satisfaction. In conclusion, Wardah enterprise ought to raise and keep the brand image, price perception and the quality of product in order to gain the customers loyalty toward Wardahâs products and always giving a satisfaction to the customers. Key words: Brand Image, Price Preception, Productâs Quality, Satisfaction, Loyalty